Parallel Optimization of the Balancing and Sequencing for Mixed-model Assembly Lines - Zhang, Wei; Hou, Liang; Gan, Yawen; Xu, Changhua; Bu, Xiangjian; Lin, Haojing (Manufacturing Technology Journal, 2019)
The traditional Mixed-model Assembly Lines (MMALS) balancing and sequencing serial design methods are difficult to adapt to rapidly changing requirements. From the perspective of the parallel design of balancing and sequencing, a mixed integer linear programming model for MMALS balancing and sequencing is proposed. An improved particle swarm optimization (PSO) algo-rithm was proposed, in the process of updating the optimal solution, the simulated annealing (SA) algorithm is added to make it possible to jump out of the local optimum with a certain probability and expand the solution selection to the entire population. Based on the algorithm, random coding and ascending decoding methods are proposed, the number of products and the number of tasks are coded and decoded at the same time. Verify the effectiveness of the algorithm by an example.
Keywords: Mixed-model assembly lines; Balancing; Sequencing; Particle swarm optimization algorithm